Exploration of the impact of genetic counselling and patient support group involvement on retinal degenerative disorders (RDD) patients: a qualitative study - Goliath, Rene (Division of Human Genetics, 2018)
This study explored the experiences of individuals within the clinical genetic service in South Africa, with inherited retinal disease. Methods: This qualitative research was based on a grounded theory approach. Semi-structured interviews were carried out after obtaining approval from the University of Cape Town Research and Ethics committees as well as from study participants themselves. Ten willing individuals were interviewed using an open-ended question guide to extract information about their experiences with vision loss including but not exclusively, concerning participants knowledge about their condition, ability to make decisions and their adaptation experiences. Interviews were audio recorded, transcribed verbatim and a reiterative thematic analysis performed on the raw data. Results: A range of themes and sub-themes emerged from the data that marked participants' experiences from the time of onset of vision loss. The main broad themes include "a roller coaster journey," "learning how to survive," "a genetic condition affecting the back of the eye, and "paving the way forward." Conclusions: The four themes presented in an almost linear fashion, marking a journey patients experienced from the onset of symptoms to the time of the interview. The initial stage of their journey was marked by difficulties and challenges exacerbated by the psychopathological responses reported in this dissertation. This stage was perceived to be prolonged and often extended into adulthood. The messages from the data support a view that the diverse and extended nature of this initial period was due to the limited support this group of participants received from the low vision specialists they consulted with. A significant impression of frustration and disillusionment was experienced by participants on not receiving information and guidance from these health care providers. Various mechanisms of support and control positively influenced patients' learning how to cope and survive their journey with visual impairment. Coping, learning what their condition is, what the causes are and the risks involved for future generations, empowered the participants in this study to obtain a view of a future for themselves and to make relevant decisions and choices necessary to realise the way ahead. Taken together though, continued education was deemed worthwhile.